Optimization of Employee Performance Cost Risk Management with the Hungarian Method using POM QM Software on XYZ MSMEs - Hukom, Cornelia Adriana; Tewu, Denny; Gunawan, Indra (Penerbit Goodwood, 2025)
Purpose: This research aims to optimize the risk management of employee performance costs in XYZ MSMEs through the application of the Hungarian method and the use of POM QM software.Methodology/Approach: The study focuses on identifying, measuring, and mitigating risks related to labor cost allocation through the Hungarian method, which is designed to minimize employee performance costs by taking into account differences in abilities, experiences, and skills among employees.Results/Findings: This study compares manual calculations and POM QM software, confirming that the Hungarian method effectively reduces labor cost risks and improves HR efficiency in XYZ MSMEs. The results show that this method minimizes cost uncertainty and helps mitigate long-term financial risks, making resource management more effective.Conclusions: The application of the Hungarian method and risk management in XYZ MSMEs effectively optimizes employee assignment, reducing labor cost risks and improving operational efficiency. Utilizing POM QM software further enhances decision-making by simplifying calculations and visualizing optimal solutions for better risk mitigation.Limitations: This study is limited to the availability of valid data in XYZ MSMEs, the relevance of the Hungarian method and POM QM for other MSMEs, and does not take into account external factors and the required technical expertise.Contributions: This study offers a practical solution to optimize the risk management of employee performance costs in MSMEs XYZ using the Hungarian and POM QM methods, thereby improving resource allocation and operational efficiency.